Changing the lanes to overtake: exploring China’s strategy of innovation - Mai, Jianjun (Cita Konsultindo, Magetan, East Java, Indonesia, 2025)
This article explores China's strategic approach to development, known as Lane- Change Overtaking (Huandao Chaoche), which emphasizes innovation, differentiation, and systemic coordination to bypass traditional development stages. Using a qualitative, interpretive approach based on multiple case studies from key sectors—including electric vehicles, artificial intelligence, and commercial drones—this study analyzes how China has successfully circumvented conventional development paths through strategic innovation and coordination. The research employs thematic content analysis of secondary data drawn from scholarly literature, official policy documents, industry reports, and credible news sources, guided by theories of latecomer advantage, disruptive innovation, and ecosystem building. This strategy involves identifying new tracks and building sufficient driving force to achieve leadership, as exemplified by China's success in the electric vehicle industry and its surge in patent applications. The core principles of Lane-Change Overtaking include aligning internal development needs with global trends, breaking path dependence, fostering disruptive innovation, and building robust ecosystems. The lessons derived from China's experiences offer valuable insights for developing nations, particularly Muslim countries, seeking to accelerate progress and enhance their global competitiveness through strategic adaptation of these principles to their unique socio-economic contexts.